1995
DOI: 10.1192/bjp.167.5.635
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of Cognitive Behaviour Therapy with Buspirone or Placebo in Panic Disorder with Agoraphobia

Abstract: Buspirone enhanced the effects of cognitive behaviour therapy on generalised anxiety and agoraphobia in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 11 publications
0
18
0
3
Order By: Relevance
“…The combination was superior to psychological therapy alone in the vast majority of studies (Barlow et al 2000;Cottraux et al 1995;de Beurs et al 1995;Gladsjo et al 2001;Marks et al 1993;Mavissakalian and Michelson 1986;Oehrberg et al 1995;Stein et al 2000;Telch et al 1985;Zitrin et al 1980Zitrin et al , 1983, whereas only two studies showed no difference between combined treatment and psychological therapy (Marks et al 1983;Sharp et al 1997). Despite statements implying the opposite, there is no methodologically sound study showing that drugs lessen the gains with CBT.…”
Section: Monoamine Oxidase Inhibitors (Maoi)mentioning
confidence: 99%
“…The combination was superior to psychological therapy alone in the vast majority of studies (Barlow et al 2000;Cottraux et al 1995;de Beurs et al 1995;Gladsjo et al 2001;Marks et al 1993;Mavissakalian and Michelson 1986;Oehrberg et al 1995;Stein et al 2000;Telch et al 1985;Zitrin et al 1980Zitrin et al , 1983, whereas only two studies showed no difference between combined treatment and psychological therapy (Marks et al 1983;Sharp et al 1997). Despite statements implying the opposite, there is no methodologically sound study showing that drugs lessen the gains with CBT.…”
Section: Monoamine Oxidase Inhibitors (Maoi)mentioning
confidence: 99%
“…Expectations were self-rated by a scale used in a previous trial for agoraphobia [34, 35]ranging from 0 (i.e. ‘The treatment will help me a lot’) to 8 (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Each scale ranged from 0 to 8. This scale was derived from the French version of Marks’s QOL scale for agoraphobia which was used in a previous trial [34, 35]and adapted for social phobia. The higher the scale, the more QOL was impaired.…”
Section: Methodsmentioning
confidence: 99%
“…The permanency of what is learned in therapy (i.e., skills, behaviors, etc.) is believed to be one of the reasons that the effects of CBT tend to be superior to pharmacological approaches at follow-up assessments (Barlow, Gorman, Shear, & Woods, 2000;Cottraux et al, 1995;de Beurs, van Dyke, Lange, & van Balkom, 1999).…”
mentioning
confidence: 99%